Adolescent "Saxophone Penis" Secondary to Crohn's Disease: Misdiagnosed as Being Posttraumatic. Issue 1 (January 2016) - Marshall, Claire; Markiewicz, Dorota; Bewley, Anthony
Abstract: We describe a patient with a "saxophone penis" mistakenly diagnosed as having posttraumatic changes. A careful history and attention to blood tests at presentation may have alerted clinicians that there was a nontraumatic cause for our patient's disease. It is essential that clinicians consider "metastatic" anogenital Crohn's disease as a possible cause of "saxophone penis".